2006
DOI: 10.1177/089686080602600222
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in an Animal Model of Chronic Peritoneal Exposure

Abstract: Objectives Acute infection in an animal model of chronic peritoneal dialysis (PD) induces structural changes in the peritoneum and alters functional characteristics of transport. These changes may compromise observations of the chronic effects of dialysis solutions. To test the hypothesis that antibiotics would prevent acute infection without affecting transport and structural properties, we characterized the frequency of infection in our rat model of PD and examined whether the inclusion of antibiotics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Therefore, some authors opt for routine addition of antibiotics. 25,26 Such an approach was used in 103 studies. The most common antibiotic was gentamicin (45%; 46 of 103), and more than one antibiotic was used in 63% (65 of 103) of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some authors opt for routine addition of antibiotics. 25,26 Such an approach was used in 103 studies. The most common antibiotic was gentamicin (45%; 46 of 103), and more than one antibiotic was used in 63% (65 of 103) of studies.…”
Section: Resultsmentioning
confidence: 99%
“…PD should be restarted after the infection is treated. In severe cases, it may be necessary to arrange for catheter replacement or even PD termination ( 53 ).…”
Section: Potential Complications In the Preparation Of A Pd Modelmentioning
confidence: 99%
“…The size of nanoparticles has a substantial effect on endocytosis in cancer cells. An appropriate size helps promote the accumulation of drugs in the tumor, inappropriate size being counterproductive (Zutter et al., 1998 ; Choi et al., 2006 ; Wong et al., 2011 ). Studies have shown that the particle sizes of polymer micelles after drug loading is larger than those that are unloaded, so that the entire drug loading system requires careful consideration (Shuai et al., 2004a , 2004b ; Elhasi et al., 2007 ).…”
Section: Strategies For Promoting Penetration Of Nano-drugsmentioning
confidence: 99%